2006
DOI: 10.1177/0093854806286451
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Juvenile Offenders According to Risk of Recidivism

Abstract: Structured risk assessment instruments are increasingly used in juvenile justice systems to support judicial decision making. They help juvenile justice authorities identify youths with a higher likelihood of repeat delinquency and reduce discretion associated with disposition decision making. To be effective, these instruments should be accurate across diverse populations. This study describes the predictive validity of the North Carolina Assessment of Risk (NCAR) in a sample of 9,534 adjudicated juveniles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 25 publications
(26 reference statements)
8
100
1
Order By: Relevance
“…In general, males are more likely to recidivate than females (e.g., Baffour, 2006;Dembo, Schmeidler, Nini-Gough, Sue, Borden, & Manning, 1998;Minor, Hartmann, & Terry, 1997;Schwalbe, Fraser, Day, & Cooley, 2006; but see Benda, Corwyn, & Toombs, 2001). Race and ethnicity are also associated with recidivism, such that individuals who are of a minority race or ethnicity are at greater risk of recidivism (e.g., Dembo et al, 1998;Minor et al, 1997;Schwalbe et al, 2006; but see Baffour, 2006). Age has also been associated with recidivism (e.g., Minor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, males are more likely to recidivate than females (e.g., Baffour, 2006;Dembo, Schmeidler, Nini-Gough, Sue, Borden, & Manning, 1998;Minor, Hartmann, & Terry, 1997;Schwalbe, Fraser, Day, & Cooley, 2006; but see Benda, Corwyn, & Toombs, 2001). Race and ethnicity are also associated with recidivism, such that individuals who are of a minority race or ethnicity are at greater risk of recidivism (e.g., Dembo et al, 1998;Minor et al, 1997;Schwalbe et al, 2006; but see Baffour, 2006). Age has also been associated with recidivism (e.g., Minor et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, youths with learning disabilities who experience involvement in special education programs are more likely to be involved in delinquency and recidivate (e.g., Archwamety & Katsiyannis, 1998, 2000Doren, Bullis, & Benz, 1996;Katsiyannis & Archwamety, 1997). Recidivism has also been shown to be influenced by the nature of the offense in the youth's criminal record (e.g., Dembo et al, 1998;Myner, Santman, Cappelletty, & Perlmutter, 1998;Schwalbe et al, 2006), with more serious prior offenses increasing the odds of recidivism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings demonstrated that being on probation in City A was a significant predictor of probation failure, unlike probationers in City B, a finding that must be assessed with caution as it has been argued that examinations of differential prediction should be subject to more stringent statistical techniques (i.e., multilevel models as opposed to traditional regression analysis, e.g., see Onifade, Davidson, & Campbell, 2009;Schwalbe, Fraser, Day, & Cooley, 2006). Doing so would allow for a more intricate understanding of the impact that community and sociopolitical variables have on the outcome measure under question, as these factors have been shown to have a different expression within minority communities.…”
Section: Discussionmentioning
confidence: 62%